2021
DOI: 10.3389/fcell.2021.602450
|View full text |Cite
|
Sign up to set email alerts
|

Onecut Regulates Core Components of the Molecular Machinery for Neurotransmission in Photoreceptor Differentiation

Abstract: Photoreceptor cells (PRC) are neurons highly specialized for sensing light stimuli and have considerably diversified during evolution. The genetic mechanisms that underlie photoreceptor differentiation and accompanied the progressive increase in complexity and diversification of this sensory cell type are a matter of great interest in the field. A role of the homeodomain transcription factor Onecut (Oc) in photoreceptor cell formation is proposed throughout multicellular organisms. However, knowledge of the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 103 publications
(126 reference statements)
0
7
0
Order By: Relevance
“…46,47 Encouragingly, a recent analysis of Ciona ONECUT revealed changes in gene expression of synaptic transmission molecules upon manipulation of ONECUT function in photoreceptor differentiation. 48 Another recent study revealed that ONECUT proteins can indeed induce neuronal features in a fibroblast-to-neuronal reprogramming approach in vitro. 49 Vertebrate ONECUT and CUX homologs are expressed in the nervous system, 46,47 but a systematic, comparative, and side-by-side analysis of all family members remains to be conducted to assess how broadly all family members cover the entire nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46,47 Encouragingly, a recent analysis of Ciona ONECUT revealed changes in gene expression of synaptic transmission molecules upon manipulation of ONECUT function in photoreceptor differentiation. 48 Another recent study revealed that ONECUT proteins can indeed induce neuronal features in a fibroblast-to-neuronal reprogramming approach in vitro. 49 Vertebrate ONECUT and CUX homologs are expressed in the nervous system, 46,47 but a systematic, comparative, and side-by-side analysis of all family members remains to be conducted to assess how broadly all family members cover the entire nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased sensitivity to aldicarb correlates with a reduction in synaptic transmission. 48 Worms were tested every 30 min for paralysis by touching the head and tail three times each. The data are presented as the percentage of moving worms at the indicated time point; dots represent the mean of independent experiments for each genotype.…”
Section: Dosage-dependent Requirement Of Cut Homeobox Genes For Pan-n...mentioning
confidence: 99%
“…By using the technology of optogenetics, the research of many difficult diseases has been advanced greatly. Using optogenetics to induce the differentiation of neural progenitor cells, the researchers were able to treat stroke in mice ( Yu et al, 2019 ; Peters et al, 2021 ; Vassalli et al, 2021 ). The mice were able to remove and reactivate a memory by changing the connections between related neurons in the brain with different frequencies of light ( Nabavi et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…A truly nervous system-wide analysis of the function of CUX or ONECUT genes in vertebrates has been missing; instead, several of vertebrate CUT or ONECUT homeodomain proteins have been well-studied in specific cellular contexts (Kropp and Gannon, 2016; Weiss and Nieto, 2019). Encouragingly, a recent analysis of Ciona ONECUT revealed changes in gene expression of synaptic transmission molecules upon manipulation of ONECUT function in photoreceptor differentiation (Vassalli et al, 2021). Our genetic loss of function analysis in C. elegans predicts that compound mutants may need to be generated in mice to assess CUT family function in vertebrate pan-neuronal gene expression.…”
Section: Discussionmentioning
confidence: 99%